Enzymatic Synthesis of Base-Functionalized Nucleic Acids for Sensing, Cross-linking, and Modulation of Protein-DNA Binding and Transcription - Hocek, Michal (Accounts of chemical research, 2019)
Protein-DNA interactions are important in replication, transcription, repair, as well as epigenetic modifications of DNA, which involve methylation and demethylation of DNA resulting in regulation of gene expression. Understanding of these processes and chemical tools for studying and perhaps even modulating them could be of great relevance and importance not only in chemical biology but also in real diagnostics and treatment of diseases. In the past decade, we have been working on development of synthesis of base-modified 2'-deoxyribo- or ribonucleoside triphosphates (dNTPs or NTPs) and their use in enzymatic synthesis of modified nucleic acids using DNA or RNA polymerases. These synthetic and enzymatic methods are briefly summarized with focus on recent development and outlining of scope, limitations, and further challenges. The main focus of this Account is on applications of base-modified nucleic acids in sensing of protein-DNA interactions, in covalent cross-linking to DNA-binding proteins ,and in modulation of protein-DNA binding and transcription. Several environment-sensitive fluorescent nucleotides were incorporated to DNA probes which responded to protein binding by light-up, changing of color, or lifetime of fluorescence. Using a cyclodextrin-peptide transporter, fluorescent nucleotides can be transported through the cell membrane and incorporated to genomic DNA. Several dNTPs bearing reactive groups (i.e., vinylsulfonamide or chloroacetamide) were used for polymerase synthesis of DNA reactive probes which cross-link to Cys, His, or Lys in peptides or proteins. An attractive challenge is to use DNA modifications and bioorthogonal reactions in the major groove of DNA for modulation and switching of protein-DNA interactions. We have systematically explored the influence of major-groove modifications on recognition and cleavage of DNA by restriction endonucleases and constructed simple chemical switches of DNA cleavage. Systematic study of the influence of major-groove modifications on transcription with bacterial RNA polymerases revealed not only that some modified bases are tolerated, but also that the presence of 5-hydroxymethyluracil or -cytosine can even enhance the transcription (350 or 250% compared to native DNA). Based on these results, we have constructed the first chemical switch of transcription based on photocaging of hydroxymethylpyrimidines in DNA by 2-nitrobenzyl protection (transcription off), photochemical deprotection of the DNA (transcription on), and enzymatic phosphorylation (only for 5-hydroxymethyluracil, transcription off). Although it has been so far demonstrated only in vitro, it is the proof-of-principle first step toward chemical epigenetics.
Keywords: DNA řízené RNA-polymerasy; DNA-dependentní DNA-polymerasy; DNA vazebné proteiny; světlo; DNA-Binding Proteins; ribonukleotidy; Ribonucleotides; DNA sondy; Protein Binding; Transcription, Genetic; Light; DNA-Directed DNA Polymerase; DNA; vazba proteinů; DNA Probes; DNA-Directed RNA Polymerases; genetická transkripce